In Silico Pharmacokinetics Study of 2,5-Dibenzylidenecyclopentanone Analogs as Mono-Ketone Versions of Curcumin - Marbun Prajona; Hakim Arief Rahman; Sri Octa Ujiantari Navista; Sulistyo Ari Sudarmanto Bambang; Endro Nugroho Agung (BIO Web of Conferences, 2023)
The absorption-distribution-metabolism-excretion (ADME) profile is a crucial parameter that indicates the pharmacokinetics of the drug. The pharmacokinetic properties of a drug represent the fate of the drug in the body. Curcumin is a main compound in turmeric produced by plants of the Curcuma longa species, and has several pharmacological effects in animal and human clinical studies. However, preclinical and clinical studies have shown that curcumin has pharmacokinetic limitations such as poor bioavailability and rapid metabolism which restrict its widespread use. Therefore, various modifications and synthesis of some analogs using curcumin as a lead compound with variations in the main structure and attached substituents have been carried out to explore the pharmacological effects as drug candidates. One of the widely developed methods is the modification of curcumin’s main structure, specifically the conversion from diketone to mono-ketone.In 1997, 2,5-dibenzylidene cyclopentanone analogs were synthesized and their biological activity were performed. However, there is no further information related their pharmacokinetic properties. Therefore, those properties were predicted by performing ADME calculation in two online servers, ADMETsar 2.0 and ADMETlab 2.0.. By utilizing the online servers ADMETsar 2.0, and ADMETLab 2.0 for in-silico screening of pharmacokinetic properties, from the 17 compounds, it was found that the variation among pharmacokinetic aspects was observed, either decreasing or increasing drug likeness properties of 2,5-dibenzylidene cyclopentanone analogs compared to curcumin. In addition, the interaction those analogs with protein or enzymes involved during ADME process such as blood plasma protein (albumin), p-Glycoprotein, and CYP3A4 was evaluated by performing molecular docking.. The docking results showed a sufficiently positive correlation with ADME screening outcomes.